The link between eco-innovation and business performance: a Taiwanese industry context - Cheng, Colin C. J.; Yang, Chen-lung; Sheu, Chwen (My University, 2014)
In practice, there are various types of eco-innovation. While each type of innovation has its own attributes, determinants, and contribution to business performance, it is not effective to implement eco-innovation programs without a holistic view. This study draws from the resource-based view theory to investigate inter-relationships among three types of eco-innovation (process, product, organizational) and their relative impact on business performance. Using structural equation modeling with 121 samples collected from Taiwan Environmental Management Association, we find that eco-organizational innovation has the strongest effect on business performance. Additionally, eco-process and eco-product innovations partially mediate the effects of eco-organizational innovation, and eco-product innovation mediates eco-process innovations' effects on business performance. Business performance is directly and indirectly affected by eco-organizational, eco-process, and eco-product innovations. The findings suggest that, in order to develop effective eco-innovation programs, managers must understand the interdependence and co-evolutionary relationships between different types of eco-innovation. Overall, this study extends the discussion of innovation to the area of environmental innovation or eco-innovation.
Keywords: Eco-innovation; Green innovation; Sustainability; Environmental management